The Effect of Lasy Extracurricular Activities on the Problem Solving Ability of Children Aged 4-5 Years - Kharisma Putri; Naili Rohmah (Journal of Educational Sciences, 2026)
Problem solving skills constitute an important aspect of early childhood cognitive development because they support children’s ability to identify problems, formulate solutions, make decisions, and evaluate outcomes. Appropriate stimulation requires exploratory learning experiences through concrete learning activities. This study aims to analyze the effect of Lasy extracurricular activities on the problem solving skills of children aged 4-5 years. The study employed a quantitative approach using a quasi experimental method with a non equivalent control group design. Research subjects consisted of 40 children, including 20 children in the experimental group and 20 children in the control group. Data analysis involved the Wilcoxon Signed Rank Test and the Mann-Whitney test. Findings indicated that the experimental group’s average score increased from 25.90 to 41.45, while the control group's score increased from 25.00 to 36.45. Statistical analysis showed a significance value of 0.000 in the Wilcoxon test and a p-value of 0.007 in the Mann-Whitney test (p < 0.05). The findings demonstrate that Lasy extracurricular activities significantly improve the problem solving skills of children aged 4-5 years and can be utilized as an alternative for cognitive stimulation through constructive play in early childhood education.